Foundation of Legal Education: The Role of Academic Lyceums in Preparing Future Lawyers - Fayziyev Javlon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This scientific article systematically analyzes the role and importance of academic lyceums as the initial link in preparing highly qualified legal professionals within the framework of comprehensive reforms aimed at improving the quality and competitiveness of the continuous legal education system in the Republic of Uzbekistan. As the object of the research, the activities of the Samarkand Regional Academic Lyceum under Tashkent State University of Law, its legal and pedagogical potential, and its strategic functions in shaping the foundation of future lawyers are comprehensively examined. The article studies the legal framework of specialized legal educational institutions, particularly the Decree of the President of the Republic of Uzbekistan No. PF-5987 dated April 29, 2020, “On Measures to Fundamentally Improve Legal Education and Science in the Republic of Uzbekistan and Further Develop the System of Training Legal Personnel,” as well as the norms of the Law of the Republic of Uzbekistan “On Education.” Based on the requirements of these normative legal acts, the study explores the introduction of modern pedagogical and information-communication technologies, including “Legal Tech” elements, into the educational process of the academic lyceum. The author theoretically and practically analyzes the methodology for developing students’ fundamental knowledge in state and legal theory, constitutional law, and other core legal disciplines. Furthermore, the mechanisms for integrating lyceum graduates into higher legal educational institutions, including Tashkent State University of Law, law faculties, and international universities, as well as improving their legal thinking, professional ethics, and legal culture, are comparatively evaluated. The article also generalizes the unique experience of the Samarkand Regional Academic Lyceum in identifying talented youth, adapting them to judicial and legal reforms, and educating them in the spirit of patriotism. Based on the analysis, scientific and practical recommendations are proposed to further improve the curricula of legal academic lyceums, strengthen the integration of theoretical and practical training through the cluster system, and enhance the intellectual potential of future legal professionals.